2006
DOI: 10.1016/s0004-9514(06)70047-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endotracheal suction on lung dynamics in mechanically-ventilated paediatric patients

Abstract: Endotracheal suctioning is performed regularly in ventilated infants and children to remove obstructive secretions. The effect of suctioning on respiratory mechanics is not known. This study aimed to determine the immediate effect of endotracheal suctioning on dynamic lung compliance, tidal volume, and airway resistance in mechanically-ventilated paediatric patients by means of a prospective observational clinical study. Lung mechanics were recorded for five minutes before and five minutes after a standardised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 22 publications
2
43
1
4
Order By: Relevance
“…This finding is consistent with a study of oxygenation and hemodynamic changes with suction in ventilated children (4) but is somewhat surprising in light of in vitro studies (15,17). In contrast, in another pediatric study catheter size was implicated in reduction in dynamic compliance after suction (19). The suction pressure in this study was 360 mm Hg (48 kPa), higher than in our study or that of Singh et al (4).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with a study of oxygenation and hemodynamic changes with suction in ventilated children (4) but is somewhat surprising in light of in vitro studies (15,17). In contrast, in another pediatric study catheter size was implicated in reduction in dynamic compliance after suction (19). The suction pressure in this study was 360 mm Hg (48 kPa), higher than in our study or that of Singh et al (4).…”
Section: Discussionsupporting
confidence: 92%
“…In the clinical setting, airway pressure and V T are likely to be influenced by the volume and consistency of mucus. Secretions adhering to the ETT can cause considerable narrowing of the ETT lumen (21,22), which could result in greater loss of pressure and V T during suction, whereas secretions entering the catheter will tend to inhibit a fall in pressure (26). However, suction in the absence of secretions can occur in clinical practice (26) and may occur toward the end of the procedure when secretions have been cleared, especially with multiple passes of the catheter.…”
Section: Discussionmentioning
confidence: 99%
“…An improvement in Wang's score in all children with bronchiolitis (100%) after being treated with actual techniques of chest physical therapy (PSE and CRR) was found in a Postiaux's et al 10 study, but without a control group. Another study found an initial increase in airway resistance and a reduction of the late auto PEEP by 13%, which would be indicative of a reduction hyperinflation 22 . We have assumed, thus, an improvement in the resistance with an increase by 50% after suctioning the upper airways because infants, until the sixth month of life, present as nose breathers.…”
Section: Sample Sizementioning
confidence: 92%